Wróć do szkoły sześciolatku - czyli o kompetencjach społecznych i emocjonalnych dzieci w świetle badań = Six-year-olds, come back to school! - on social and educational competence of children in light of studies - Kruszewska, Aleksandra; Nazaruk, Stanisława (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The Act of November 13, 2013 made education of six-year-old children compulsory. Two years later, on December 29, 2015, this obligation was abolished. One of the reasons for this was the widely proclaimed lack of su?cient emotional competence of children. The achievement of good pre-school education is veri?ed through the achievement of school readiness by children - visible in good social and emotional preparation adequate to their age. The article is a report on studies that compare social and emotional abilities of children (on the basis of their emotions and feelings) who have completed their pre-school education and are to start school.
Keywords: kompetencje społeczne; kompetencje emocjonalne; sześciolatek; siedmiolatek; dojrzałość szkolna; emocje; uczucia; social competences; emotional competence; six-year-olds; seven-yearolds; school readiness; emotions; feelings